Why does maxillary skeletal expansion work with some adults and fail with Others?: A narrative review - Amira Allam; Basaruddin Ahmed; Norma Ab Rahman (Elsevier, 2024)
Maxillary skeletal expansion is considered a challenging treatment modality in adult ages. Mini-screw-assisted rapid palatal expansion (MARPE) is considered a pioneer in providing a solution for maxillary deficiency in adults away from any surgical interventions. If we consider patient cooperation and motivation, together with operator skills, as constant factors during MARPE, and exclude all hygiene and soft tissue complications that jeopardise the appliance's stability, there is a percentage of expansion failure recorded in different studies with no emphasis on what makes mid-facial diastema appear in some, rather than others. Electronic databases including PubMed, Scopus, Google Scholar, and Web of Science, were searched for literature published in English till 2023. Failure was related in some literature to different criteria, as of yet, no verifiable indicators would allow us to determine success or failure in advance. This review highlighted the most common reasons for failure discussed in different literature: Chronological Age, Mid-palatal suture maturation, Bone density, Sex, Race, Appliance design, and Expansion technique used. This study could be considered an attempt to make candidate selection for non-surgical maxillary skeletal expansion at this old age easier, time-saving, and cost less.